Screening homeless Veterans for a voluntary money management skills training program. Issue 4 (2nd October 2017) - Iheanacho, Theddeus; Ablondi, Karen; Stefanovics, Elina; Rosen, Marc; Rosenheck, Robert
ABSTRACT: This study seeks to examine need, interest, and participation in recovery-oriented, voluntary money-management training groups among homeless Veterans. Veterans experiencing homelessness ( N  = 213) completed a 10-item questionnaire (Ask for Training in Money Management [ATMM]) concerning their experience of their financial status, problems with money management, and interest in a voluntary money-management program. Exploratory factor analysis (EFA) identified the structure of the survey responses. Pearson correlation coefficients were used to examine the association of sociodemographic and diagnostic data with the identified money-management need factors, interest in, and subsequent attendance at recovery-oriented money management (ROMM) training groups. EFA yielded a two-factor solution. Factor 1 represented "satisfaction with the amount of funds" respondents had. Factor 2 represented "problems with money management." Interest in ROMM was most strongly associated with experience of difficulty managing funds. Altogether 49 (23%) subsequently participated in the ROMM groups. Participation was associated with expressed interest in ROMM, feeling dissatisfied with available funds, and, less strongly, with difficulty managing funds. ATMM successfully elicited subjective feelings about financial status and money management. It identified interest in seeking help and predicted, and apparently promoted, engagement and participation in voluntary money-management groups with emphasis on personal choice and autonomy.